Activity Contents Of Mathematical Communication In Merdeka Curriculum Textbooks Of Grade VII On Plane Geometry Materials - Tri Sedya Febrianti; Jarnawi Afgani Dahlan; Siti Fatimah (PAEDAGOGIA, 2024)
This research was conducted to analyze the availability of activity content in curriculum merdeka textbooks of grade VII on plane geometry materials published by the Ministry of Education and Culture of the Republic of Indonesia. The research method was carried out in a descriptive qualitative manner with the type of textbook content analysis. Mathematical communication indicators are used as the aspect of analysis. The research results obtained are that all activities in this book have been able to support the improvement of students' mathematical communication competence, although there are no special labels or instructions related to mathematical communication indicators embedded in each activity so that the meaning is still implied or based on the opinion of researchers with adjusted theory used in relation to mathematical communication. From the data analysis that has been done, it can be concluded that the content material is good enough based on the percentage category table for the suitability of book activity, which is equal to 39%. Based on the research this books can help students develop their mathematical communication ability  with teacher guidance. However, basically this book provides sufficient activities as an effort to improve students' mathematical communication skills if teachers are able to use this book well as a resource and learning media in the classroom